Factors associated with prefectural level physical activity in Japan: An ecological study - Noboru Horinouchi; Yuki Kataoka; Kyoko Yamamoto; Seiji Shiota; Eishi Miyazaki (Journal of General and Family Medicine)
Abstract Background Physical activity inequalities are an important global concern; nonetheless, few studies have comprehensively examined the association between physical activity inequalities and related factors. We aimed to explore factors associated with regional inequalities in physical activity in Japan. Methods We investigated the relationship of individual, psychological/behavioral, social, and built‐environmental factors with the proportion of individuals with exercise habits across Japanese prefectures. We sourced data from open databases, including the Japanese National Health Insurance Claims and Nationwide Screening Program Database. We defined exercise habits as engaging in at least 30 min of moderate exercise at least twice a week. We employed multiple regression analysis to identify factors associated with prefectural level physical activity. Results The median proportion of individuals with exercise habits was 27% (interquartile range, 25–29). Higher frequency of exercise habits was associated with higher frequency of history of exercise (coefficients, 0.60; 95% confidence interval, 0.41–0.80) and lower proportion of female gender (coefficients, −1.74; 95% confidence interval, −2.80 to −0.69). Conclusions Exercise history and female gender may be related to prefectural level physical activity in Japan. Physical activity interventions should be promoted among women without exercise history.